Comparison of Antibody Levels Produced by Pfizer, AstraZeneca, and Sinopharm Vaccination in COVID-19 Patients in Erbil City-Iraq: Immune Response Against Vaccination in COVID-19 Patients - Majed, Sevan Omer (Cellular and Molecular Biology, 2023)
In this study, early adverse impacts that emerged after vaccination with each dose of these vaccines were compared from previously infected participants. Ant-SARS-CoV-2 spike-specific IgG and IgA antibodies produced by these three vaccines have been assessed using ELISA method at different time periodsꓼ including pre-vaccination, 25 days after the first shot of vaccination and 30 days after the second shot of vaccination with Pfizer-BioNTech, AstraZeneca, and Sinopharm vaccine. Overall, 150 previously infected cases were studied, 50 cases received Pfizer vaccine, 50 cases received AstraZeneca vaccine, and 50 cases received Sinopharm vaccine. The findings showed that a higher number of vaccinated participants with AstraZeneca and Pfizer vaccine had tired/fatigue/lethargy, headache, fever, and sore in arm at the first shot, but milder adverse effects, such as headaches, fever, and sore in arm, were detected in the data on the Sinopharm vaccine's adverse impacts. At the second dose, a lower number of vaccinated cases with AstraZeneca and Pfizer vaccine reported higher frequencies of the side effects. However, the results showed that the level of anti-spike-specific IgG and IgA antibodies produced by vaccinated patients with Pfizer vaccine increased compared to those who vaccinated with AstraZeneca and Sinopharm vaccine from 25 days after the first dose. From 30 days after the second dose, the IgG and IgA antibodies were significantly boosted in 97% of vaccinated patients with Pfizer vaccine compared to 92% of those who vaccinated with AstraZeneca vaccines and 60% of those who vaccinated with Sinopharm. In conclusion, these results confirmed that two doses of the Pfizer, and AstraZeneca vaccine induce a higher response of IgG and IgA antibodies than that induced by Sinopharm vaccines.